Inhibition of iNKT Cells by the HLA-G-ILT2 Checkpoint and Poor Stimulation by HLA-G-Expressing Tolerogenic DC - Wu, Ching-Lien; Caumartin, Julien; Amodio, Giada; Anna, François; Loustau, Maria; Gregori, Silvia; Langlade-Demoyen, Pierre; LeMaoult, Joel (Frontiers in Immunology, 2021)
Invariant Natural Killer T (iNKT) cells are a small and distinct population of T cells crucial in immunomodulation. After activation by alpha-GalactosylCeramide (αGC), an exogenic glycolipid antigen, iNKT cells can rapidly release cytokines to enhance specific anti-tumor activity. Several human clinical trials on iNKT cell-based anti-cancer are ongoing, however results are not as striking as in murine models. Given that iNKT-based immunotherapies are dependent mainly on antigen-presenting cells (APC), a human tolerogenic molecule with no murine homolog, such as Human Leucocyte Antigen G (HLA-G), could contribute to this discrepancy. HLA-G is a well-known immune checkpoint molecule involved in fetal-maternal tolerance and in tumor immune escape. HLA-G exerts its immunomodulatory functions through the interaction with immune inhibitory receptors such as ILT2, differentially expressed on immune cell subsets. We hypothesized that HLA-G might inhibit iNKT function directly or by inducing tolerogenic APC leading to iNKT cell anergy, which could impact the results of current clinical trials. Using an ILT2-transduced murine iNKT cell line and human iNKT cells, we demonstrate that iNKT cells are sensitive to HLA-G, which inhibits their cytokine secretion. Furthermore, human HLA-G+ dendritic cells, called DC-10, failed at inducing iNKT cell activation compared to their autologous HLA-G‒ DCs counterparts. Our data show for the first time that the HLA-G/ILT2 ICP is involved in iNKT cell function modulation.